Intrapreneurship as a promoter for the development of social enterprises - Coronado Ríos, Bladimir Jesús (Cooperativismo & Desarrollo, 2022)
The focus of this paper is intrapreneurship in the city of Medellín and the metropolitan area, for the purposes and interest of establishing the main characteristics in the approach to entrepreneurship and the direct incidence between both concepts. Entrepreneurship, without a doubt, is the engine of the economy of a country, as a practice that is learned in the culture of a society, for this reason, it is essential to promote it in different scenarios, identifying the elements that promote the strengthening of entrepreneurship. Intrapreneurship as a motor for the development of social enterprises in the generation of stable employment in Medellin and the metropolitan area. This research seeks to address this situation from an entrepreneurial approach, delving into aspects that are key factors in the promotion of intrapreneurship, from a prospective view with field evaluations of different types of ventures, based on the review and implementation of tools that provide necessary and sufficient information for the establishment of strategic considerations that allow for the development of actions that promote and strengthen social entrepreneurship.